Läkartidningen medical journal 1996 - Kokkinakis, Dimitrios (University of Gothenburg, 2024)
Läkartidningen is a Swedish medical journal and the official publication of the Swedish Medical Association, the professional association and trade union for physicians in Sweden. The journal was founded in 1904 and is primarily aimed at physicians and other healthcare professionals. It publishes medical news, scientific articles, opinion pieces, clinical reviews, commentaries, and information on developments in healthcare. The journal also serves as a forum for professional issues, ethics, working conditions, and matters relating to the medical profession.

Läkartidningen är en svensk medicinsk tidskrift och organ för Sveriges läkarförbund, läkarnas fackliga organisation i Sverige. Tidskriften grundades 1904 och riktar sig främst till läkare och annan vårdpersonal. Den publicerar medicinska nyheter, vetenskapliga artiklar, debattinlägg, kliniska översikter, kommentarer och information om hälso- och sjukvårdens utveckling. Tidskriften fungerar också som ett forum för professionella frågor, etik, arbetsmiljö och läkaryrkets villkor.
Läkartidningen 1996
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik